Manajemen Risiko Barang Jaminan Pada Produk Pembiayaan Gadai Emas di BJB Syariah KCP Rawamangun - Windy Anis Syafitri; Trisna Wijaya (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2022)
Gold pawn financing is the provision of funds based on an agreement between the bank and other parties with collateral in the form of gold. BJB Syariah KCP Rawamangun still has gold collateral that doesn’t has certificate. Every financing carried out has a level of risk, including the gold pawn financing product. In some situations these risks can make the bank to be collapse, therefore this risk must be managed and controlled. Risk can be managed and controlled by implementing risk management. Based on this background, the formulation of the problem in this study is how the risk management of collateral for gold pawn financing products at BJB Syariah KCP Rawamangun. The purpose of this study was to determine the risk management of collateral on gold pawn financing products at BJB Syariah KCP Rawamangun. The method that used in this reaesearch is descriptive method with a qualitative research. With two data sources, namely primary data sources consisting of Gold Analysts and Operations Supervisors and secondary data sources consisting of supporting documents or books. The data collection techniques that used were observation, interview, and documentation. The research instrument that used was the researcher himself. The data credibility test that used was the triangulation of sources and reference materials. The data analysis technique that used consists of three stages, namely data reduction, data display and conclusions drawing or verification. Based on the results of the research that BJB Syariah KCP Rawamangun in financing gold pawning, there are risks that can come anytime and cannot be predicted, such as the risk of counterfeit gold, the risk of misjudgment, the risk of financing problems, the risk of storage, the risk of theft and the risk of natural disasters. To deal or minimize these risks BJB Syariah KCP Rawamangun implements a risk management system consisting of four stages, namely risk identification, risk measurement, risk monitoring, and risk control.